Ultrafast photoexcitation dynamics of ZnTe crystals by femtosecond optical pump‐probe and terahertz emission spectroscopy. Issue 8 (13th April 2020) - Liu, Jianrui; Chen, Xinzhong; Yao, Ziheng; Wu, Xincheng; Liu, Mengkun; Balakin, Alexey V.; Shkurinov, Alexander P.; You, Guanjun; Zhu, Yiming
Abstract: In this work we perform ultrafast optical pump‐optical probe (OPOP) and optical pump terahertz (THz) emission (OPTE) studies on the ultrafast excitation dynamics in <110> ZnTe crystals. Ultrafast two‐photon absorption and coherent phonon are revealed in OPOP measurements. Pump‐power‐ and polarization‐dependent phonon dynamics are characterized in time‐resolved transmission, reflection, and Kerr rotation using OPOP. The phonon polariton‐induced THz emission is directly observed in the time domain of OPTE dynamics. It is clear that the transverse optical phonon at ~3.7 THz and phonon polariton at ~2.6 THz are evident in OPOP measurement while OPTE only reveals part of the polariton dynamics.